2021
DOI: 10.3390/microorganisms9081723
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Supernatant from Adult with Autism Spectrum Disorder Alters Digestive Functions, Intestinal Epithelial Barrier, and Enteric Nervous System

Abstract: Autism Spectrum Disorders (ASDs) are neurodevelopmental disorders defined by impaired social interactions and communication with repetitive behaviors, activities, or interests. Gastrointestinal (GI) disturbances and gut microbiota dysbiosis are frequently associated with ASD in childhood. However, it is not known whether microbiota dysbiosis in ASD patients also occurs in adulthood. Further, the consequences of altered gut microbiota on digestive functions and the enteric nervous system (ENS) remain unexplored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 80 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…A recent investigation of fecal SCFA in constipated ASD children indicated a two-fold increase in VA concentrations associated with Acidobacteria in children with ASD compared to TD children (Hua et al, 2020). However, SCFA was not different in adults with ASD (Gonzales et al, 2021), and De Angelis et al reported that total short-and medium-chain fatty acids were significantly higher in TD individuals than in ASD individuals (De Angelis et al, 2013). Individuals with Rett syndrome (the leading monogenic cause of ASD) had less bacterial gut microbiota richness and diversity than TD individuals and displayed high levels of SCFAs, especially isovalerate and isobutyrate propionate.…”
Section: Discussionmentioning
confidence: 96%
“…A recent investigation of fecal SCFA in constipated ASD children indicated a two-fold increase in VA concentrations associated with Acidobacteria in children with ASD compared to TD children (Hua et al, 2020). However, SCFA was not different in adults with ASD (Gonzales et al, 2021), and De Angelis et al reported that total short-and medium-chain fatty acids were significantly higher in TD individuals than in ASD individuals (De Angelis et al, 2013). Individuals with Rett syndrome (the leading monogenic cause of ASD) had less bacterial gut microbiota richness and diversity than TD individuals and displayed high levels of SCFAs, especially isovalerate and isobutyrate propionate.…”
Section: Discussionmentioning
confidence: 96%
“…Still, by using cell lines and supernatants of single probiotic strains, these in vitro models have a rather limited representation of the complex situation in vivo with respect to both the gut tissue and the microbiome. Both aspects were grasped in their full complexity in a recent study by Gonzales et al , where they showed impaired intestinal digestive and barrier function upon transferring fecal supernatant of human Autism Spectrum Disorder patients into mice [ 72 ] . Although mouse models are frequently employed in biomedical research and allow for studying host-microbe interactions in a controlled setting, using a mouse model for human gut microbiota research has often limited translatability [ 73 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in early-life gut microbiota can impact host neuroimmunoregulation ( Morais et al., 2021 ). It is now understood that ASD patients typically exhibit a dysregulated intestinal epithelial barrier ( Gonzales et al., 2021 ). Similarly, an observational study found that SCFAs produced by gut microbiota metabolism could modulate the production of interleukin-2 (IL-2), and autistic patients exhibited an abnormally high level of IL-2, consistent with our GO analysis results ( Vinolo et al., 2011 ; Cao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%